2016
DOI: 10.1007/s12020-016-1020-8
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of protocols for induction of chronic hyperthyroidism in male and female mice

Abstract: Protocols for induction of hyperthyroidism in mice are highly variable and mostly involve short-term thyroid hormone (TH) treatment. In addition, little is known about a possible influence of sex on experimental TH manipulation. Here we analyzed the efficacy of intraperitoneal vs. oral levothyroxine (T4) administration to induce chronic hyperthyroidism in male and female mice and asked which T4 dosing intervals are required to achieve stable organ thyrotoxicosis. T4 was administered intraperitoneally or orally… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
20
0
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 22 publications
(23 citation statements)
references
References 21 publications
1
20
0
2
Order By: Relevance
“…2 ). This has already been observed by us in an earlier study using young mice [ 16 ] and by others using T3 [ 35 ], but was not expected to appear in older mice. Different mechanisms may be considered to contribute to this observation.…”
Section: Discussionsupporting
confidence: 78%
See 1 more Smart Citation
“…2 ). This has already been observed by us in an earlier study using young mice [ 16 ] and by others using T3 [ 35 ], but was not expected to appear in older mice. Different mechanisms may be considered to contribute to this observation.…”
Section: Discussionsupporting
confidence: 78%
“…Chronic hyperthyroidism and hypothyroidism were induced as previously described [ 13 16 ]. Briefly, for hyperthyroidism, i.p.…”
Section: Methodsmentioning
confidence: 99%
“…Patients with hyperthyroidism usually notice a loss in their body weights, which is not consistent with observations in animal models of hyperthyroidism. Previous studies have observed a reduction [18], an increase [19, 20] or no change in body weight in hyperthyroid animals [21].…”
Section: Discussionmentioning
confidence: 99%
“…Total RNA from pituitaries, thyroid gland, liver and heart was isolated using the RNeasy Kit according to the manufacturer's instruction (Qiagen, Hilden, Germany) and stored at −80°C as previously described (11). RNA was reverse transcribed into cDNA with SuperScriptIII (Life Technologies, Darmstadt, Germany) and hexamer primers.…”
Section: Quantitative Real-time Pcrmentioning
confidence: 99%